(untitled) (Sahayaatra सहयात्रा, 2026)
The Kalapani–Lipulekh–Limpiyadhura dispute constitutes a persistent point of contention in Nepal–India relations, shaped by the intersection of colonial cartographic legacies, competing territorial epistemologies, and evolving geopolitical conditions. This article analyzes the dispute through the philosophical framework of Vaiseṣika, with particular attention to the interaction of dravya (material and geographical conditions), guna (knowledge systems and interpretative practices), and karma (political agency and state action) in the production of territorial claims. Drawing on historical treaties, colonial-era maps, diplomatic records, and contemporary political developments, the study argues that the dispute originates in structural ambiguities embedded in the Treaty of Sugauli (1816), which were subsequently reinforced by British cartographic reinterpretations of the Kali River’s headwaters and later consolidated through post-colonial administrative practices. These historical contradictions were further shaped by asymmetrical power relations between Nepal and India, strategic security concerns following the 1962 Sino-Indian War, and the growing salience of territorial nationalism in Nepal after the restoration of multiparty democracy in 1990. The constitutional incorporation of Kalapani, Lipulekh, and Limpiyadhura into Nepal’s official map in 2020 represents a significant moment in which historical memory and state sovereignty were formally rearticulated within constitutional and symbolic state practice. By applying Vaiśeṣika philosophy to border analysis, this study reframes the Nepal–India territorial dispute as a historically evolving process rather than a fixed legal disagreement. It demonstrates that the border question is produced through the continuous interaction of material geography, contested knowledge systems, and political decision-making. In doing so, the paper contributes to border studies and South Asian geopolitics by offering an indigenous philosophical perspective that highlights how historical contradictions continue to structure contemporary territorial disputes.